Scalp Porocarcinoma: a Rare Diagnosis - Brasileiro, A (2013)
Adnexal skin tumours are rare conditions, and often clinically indistinguishable from other cutaneous neoplasms. Porocarcinoma, a sweat gland malignant tumour, is more commonly found on extremities. Few reports in other anatomic locations can be found in the literature, and those arising on the scalp are even scarcer. The authors report the case of an 84-year-old diabetic man, with a tumour on the left parietal region for 1 year, which histopathological features were consistent with porocarcinoma. The importance of histopathologic diagnosis is hereby emphasized by the more aggressive behaviour of this tumour, therefore requiring clinical actuation accordingly.